A PILOT STUDY ON DRIVING DIFFICULTIES AMONG BILATERAL CATARACT PATIENTS - Abd Rahman, Mohd Harimi; Abdul Mutalib, Haliza; Mohd Norizan, Nurul Hafizah; Md-Muziman-Syah, Md Mustafa (International Journal of Allied Health Sciences, 2021)
Background: The presence of cataract causes reduced visual acuity (VA) and contrast sensitivity (CS), thus it can affect individual’s daily activities and quality of life. The aim of this study was to investigate self-reported driving difficulties among patients with bilateral cataract using the Driving Difficulty Questionnaire. Methodology: This cross-sectional study involved the measurement of visual functions (VA and CS) and driving difficulty. It involved 30 bilateral cataract patients with valid driving license and were actively involved in driving. Results: The mean age of the patients were 63.23+5.39 years old. The mean composite driving difficulty score was 72.08+15.95 and most of the patients were having driving difficulty in raining situation and during nighttime. Furthermore, there was no significant correlation between driving difficulty and VA (rs=-0.26, p=0.15). However, there was a significant correlation between driving difficulty and CS (rs=0.40, p=0.03). Conclusion: This study suggests drivers with bilateral cataract would have driving difficulty, especially in low contrast situations. Keywords: driving difficulty, cataract, visual impairment